THE IMPORTANCE OF STUDENTS’ SELF EFFICACY AWARNESS IN LEARNING ENGLISH - Citra Suryanovika (STBA Pontianak, 2017)
This article reviews the importance of self-efficacy in learning English, and some ways to promote self-efficacy. Recently, self-efficacy becomes a well-known subject in learning and teaching English as a foreign language. Some former researches have shown the positive impact of self-efficacy on aca- demic performance, it is defined as a self-oriented perception in assessing his/her capability in learning English. Teachers may encourage students to en- hance their self-efficacy through some approaches. They may employ student- centred learning, accommodate students’ learning styles through varied teach- ing strategies and approaches, provide clear instruction, routine practice and feedbacks.